Six Years Observation After Successful Treatment of Bacterial Vaginosis - Jane Boris; Carl Påhlson; P.-G. Larsson (Hindawi Limited, 1997)
Objective: The cure rate after treatment of bacterial vaginosis (BV) differs in various investigations, but most studies report a cure rate of 70% after 1 month.